146 AORTIC ACCELERATION TIME/EJECTION TIME RATIO AND BI-VENTRICULAR PERFORMANCE IN SEVERE AORTIC STENOSIS. (15th December 2022) - Dotto, Alberto; Ciceri, Luca; Springhetti, Paolo; Urbani, Giulia; Del Sole, Paolo Alberto; Nistri, Stefano; D´ascenzo, Fabrizio; Gallone, Guglielmo; Tafciu, Elvin; Bergamini, Corinna; Rossi, Andrea; Luciano Ribichini, Flavio; et al.
Abstract: Introduction: Echocardiographic evaluation of severe aortic stenosis (SAS) is is important to guide the therapeutic approach but often challenging. Recent studies have demonstrated that the ratio of acceleration time/ejection time (AT/ET) is a simple and reproducible echocardiographic parameter that integrates aortic stenosis severity evaluation and adds information on patient's prognosis. Aim: The aim of the study is to investigate the role of the ratio of acceleration time (AT) and ejection time (ET) and its major determinants in severe aortic stenosis . Methods: Consecutive echocardiograms of patients with severe AS referred to our center were analyzed offline using Tomtec Arena (Tomtec, Untershlei heim, Germany). AT was measured from the start of the CW Doppler aortic wave, to the peak of the aortic jet. ET was calculated from the same starting point, to the end of the CW Doppler aortic wave. Results: A total of 135 patients with severe aortic stenosis formed the study cohort: patients with AT/ET below the median value of 0.35 (vs. higher) presented lower LVEDV (60 vs. 71 ml/mq; p 0.014), left ventricle mass index (116 vs 130 g/m2; p 0.035) and higher LVEF (58 vs 50%; p 0.001), GLS (- 14 vs - 12%; p 0.025), FAC (46 vs 41%; p 0.01), SBP (141 vs 131 mmHg; p 0.003). At multivariable analysis the major AT/ET determinants were systolic arterial pressure and bi-ventricular performance parameters. The following nested regression were created: the first inclusive of systolic arterial pressure (PAS), fractional area change (FAC), left ventricular mass indexed (LVMI), global longitudinal strain (GLS) (R2=0.48 p<0.001), the second inclusive of PAS, FAC, LVMI, GLS, AVA (R2=0.57, p<0.001), the third inclusive of PAS, FAC, LVMI, LVEF, AVA (R2=0.64, p<0.001). Conclusion: Our study demonstrated that AT/ET ratio relates quite well with LV performance in the context of SAS. An high ACT/ET ratio tends to be associated with a poor bi-ventricular performance and LV negative remodeling. It is possible that this simple parameter in the next future could help in staging the disease among SAS patients.